2015
DOI: 10.1155/2015/286989
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Effects of Acupoint Antioxidant Intervention by Measuring Electrical Potential Difference along the Meridian

Abstract: Previous studies suggest that superoxide anions are possibly traveling along acupuncture meridians. The electrical potential difference (EPD) between acupoints may be related to the movement. To test the above hypothesis, we conducted a study investigating the effects of acupoint antioxidant interventions on the meridian EPD. Firstly, ST39 (L) and ST44 (L) were screened out for the EPD detection along the stomach meridian, and ST36 (L) was selected for interventions including acumassage with the control cream,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
(11 reference statements)
0
13
0
Order By: Relevance
“…H. Chen et al, 2016). Pathology in an internal organ can alter electrical currents, resistances, and potential differences in the meridians that correspond to the internal organ (Xiao, 2012; M. M. Xu et al, 2015; X.…”
Section: Introductionmentioning
confidence: 99%
“…H. Chen et al, 2016). Pathology in an internal organ can alter electrical currents, resistances, and potential differences in the meridians that correspond to the internal organ (Xiao, 2012; M. M. Xu et al, 2015; X.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, reproducible fluorescence lines superimposable to meridian lines were revealed on the frontal interior abdominal wall when intracellular ROS indicators were injected into living SD-rats tail vein, confirming the substantial implication of ROS in meridian system [14]. A controlled study has shown that topical application of superoxide dismutase (SOD) fused with the TAT peptide (TAT-SOD), to various acupoints along the meridian lines used in acupuncture to treat obesity, leads to significant weight loss [15], monitoring the effects of acupoint antioxidant intervention by measuring electrical potential difference along the meridian [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, acupoint ST36 was stimulated by massage with and without TAT-SOD, acupuncture needle insertion, and injection of glutathione, while monitoring the electric potential difference (EPD) between two neighboring acupoints along the same meridian. The interventions of TAT-SOD massage and glutathione injection showed very similar EPD patterns to acupuncture, suggesting that acupuncture may function through a superoxide regulating mechanism, whose effect can be electrically-monitored [21].…”
Section: Introductionmentioning
confidence: 83%